IMPLEMENTASI ARTIFICIAL INTELLIGENCE DALAM DUNIA ARSITEKTUR DAN PENGARUHNYA TERHADAP PROFESI ARSITEK - Ahmad Nur Maulana Said; Diyah Daulah Auliyah Badar; Nurul Cahyani Hamzah; Muhammad Jamil Syah; Muh. Hamka Al Farizi (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This research aims to investigate the impact of artificial intelligence (AI) on the future of architecture and architects. Artificial intelligence has become an integral part of emerging technological developments, and is increasingly being utilised in various fields, including architecture. This research will examine how the application of AI in architecture affects the design process, design solutions, and the role of architects in future architectural practice. Through literature review and data analysis, this study will present information on the benefits and challenges of AI adoption in architecture as well as implications for architects. It is hoped that the results of this study can provide insight into the role of AI in the future of architecture and how architects can adapt and optimise the potential of this technology in their professional practice.